The Effectiveness Of Using The "Aplikasi Sahabat Remaja Indonesia (ASRI) And Whatsapp Reminder On Compliance With Beautiful Pill Consumption In Teenage Girl At SMKN 3 Banjarbaru - Ezliana, Ezliana; Hapisah, Hapisah; Megawati, Megawati; Rusmilawaty, Rusmilawaty (JURNAL KEBIDANAN BESTARI, 2024)
The main obstacle to giving Fe tablets comes from presdiposing factors, namely poor compliance such as forgetting, due to side effects that arise, negative perceptions about giving iron supplements. The study aims to determine the effectiveness of using the “aplikasi sahabat remaja Indonesia (ASRI)” And Whatsapp Reminder on compliance with beautiful pill consumption in teenage girl at smkn 3 banjarbaru. This research uses a quasi-experiment with a Nonequevalent Control Group Design approach. The population in this study was 272 female student at SMKN 3 Banjarbaru. The sample in this study was 74 resondents. The sampling technique is Cluster Random Sampling. The independent variables are the ASRI and Whatsapp Reminder, the dependent variable is compliance with the consumption of Fe tablet. Data were analyzed using the Wilcoxon Signed Rank Test and the Mann Whitney test with a significance of 0,05. The research results obtained compliance with p value = 0,000 (mean rank 45,0) in the ASRI group and p value = 0,008 (mean rank 30,0) in the Whatsapp Reminder group. Mann whitney test results p value 0,001, p<0,05. The conclusion of the study is a difference in effectiveness between ASRI and Whatsapp Reminder on compliance with Fe talet consumption teenage girl at SMKN 3 Banjarbaru. Expected that ASRI and Whatsapp Reminder can become a medium for monitoring the consumption of Fe tablets in teenage girl. Keyword: Fe tablets, obedience, iron substace.